An Overview of the Immunological Defenses in Fish Skin. (14th October 2012) - Ángeles Esteban, María
Abstract : The vertebrate immune system is comprised of numerous distinct and interdependent components. Every component has its own inherent protective value, and the final combination of them is likely to be related to an animal's immunological history and evolutionary development. Vertebrate immune system consists of both systemic and mucosal immune compartments, but it is the mucosal immune system which protects the body from the first encounter of pathogens. According to anatomical location, the mucosa-associated lymphoid tissue, in teleost fish is subdivided into gut-, skin-, and gill-associated lymphoid tissue and most available studies focus on gut. The purpose of this paper is to summarise the current knowledge of the immunological defences present in skin mucosa as a very important part of the fish immune system, serving as an anatomical and physiological barrier against external hazards. Interest in defence mechanism of fish arises from a need to develop health management tools to support a growing finfish aquaculture industry, while at the same time addressing questions concerning origins and evolution of immunity in vertebrates. Increased knowledge of fish mucosal immune system will facilitate the development of novel vaccination strategies in fish.